Water transportation from Islamic perspectives - Mohd Ibrahim, Nuraihan; Bachok, Syahriah; Mohamed Osman, Mariana; Abdullah, Alias (2012)
Water transportation is one of the various types of transportation modes that are widely used nowadays. This paper deals with the Islamic perspectives of water transportation. In this paper, two categories of water transportation which are inland water transport (IWT) and ocean transport are been explained. IWT is energy efficient and cheaper mode of transport for bulk commodities and has the least impact on the environment. Ocean transport is a movement of goods and passengers by ships through sea or ocean waterways. In Malaysia, the Marine Department is responsible for supervision of the maritime sector planning policy. The department is also under the jurisdiction of the Maritime Division of the Ministry of Transport. Water transportation has some environmental impacts of which will be categorized into two namely episodic and routine. Episodic pollution discharges are from the commercial industry and policy makers whereas routine pollution is released from the safe operation activities of the vessels. Lastly, this paper will elaborate on the concept of sustainable water transport. The water transportation needs to be planned and designed in a systematic and futuristic way in order to become the sustainable transport mode.